Factor yang Mempengaruhi Kesiapsiagaan Perawat Gawat Darurat dalam Manajemen Bencana: Literatur Review - Desi Holifatus Suaida; Ida Wahyuni; Tri Nili Sulayfiyah; Mery Eka Yaya Fujianti (Universitas Nazhatut Thullab Al- Muafa Sampang, 2024)
Background: A disaster is an event that threatens human life. Disasters result in high death rates, injury rates, infrastructure damage and economic losses for communities. Support from the role of hospitals and health workers, especially nurses, is very much needed to reduce the number of victims in each disaster, especially in improving disaster preparedness. The preparedness stage includes planning the number of patients, evacuating patients to hospitals, preparing medical equipment, and preparing disaster training to carry out nursing actions. Purpose: This study aims to determine the factors that influence the preparedness of health center nurses and emergency room nurses in disaster management. Methods: We used document studies to search for journals used in the literature review. The journals used in the literature review were obtained through a database-based search for international journal scienced direct, PubMed. The researcher wrote the keywords, namely